2023
DOI: 10.1186/s42836-023-00188-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of soft tissue releases in robotic assisted cementless TKA with mechanical alignment and flexion gap balancing

Abstract: Background To ensure the success of total knee arthroplasty (TKA), precise bone cuts and a well-balanced soft tissue envelope are crucial. Soft tissue release may be necessary, subject to various factors. Therefore, documenting the type, frequency, and necessity of soft tissue releases can establish a benchmark for comparing different alignment techniques and philosophies and evaluating their outcomes. The purpose of this study was to demonstrate that robotic-assisted knee surgery requires mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In our study, over 70% of patients did not require a soft tissue release as we previously reported for this group [ 16 ] and our analysis did not show any significant difference in patients’ happiness whether they required a soft tissue release or not. Abhari et al [ 17 ] reported at 1 year follow up that 93% were satisfied in the kinematic alignment group compared to 83% in the mechanical aligned group using conventional instruments [ 17 ].…”
Section: Discussionsupporting
confidence: 73%
“…In our study, over 70% of patients did not require a soft tissue release as we previously reported for this group [ 16 ] and our analysis did not show any significant difference in patients’ happiness whether they required a soft tissue release or not. Abhari et al [ 17 ] reported at 1 year follow up that 93% were satisfied in the kinematic alignment group compared to 83% in the mechanical aligned group using conventional instruments [ 17 ].…”
Section: Discussionsupporting
confidence: 73%
“…Song et al [ 22 ] concluded that RA-TKA leads to significantly less number of outliers in terms of postoperative limb alignment when compared with conventional instruments. Selvanathan et al [ 23 ], in a prospective study with 175 patients, concluded that robot assistance enhances bone cut precision in TKA, which allows titration of soft tissue balance to achieve optimal balance. Interestingly, multiple studies have reported only 80% satisfaction rate with TKA [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Weber et al reached similar conclusions as they performed manual TKAs in an average of 77.3 min, while navigated TKAs took slightly longer, with an average of 84.1 min [37]. The similar operative times can be attributed to the fact that while RA-TKAs require some preparation, this can be performed concurrently with the surgical approach of the knee; moreover, while RA-TKA involves a series of specific steps such as pin placement, knee soft tissue evaluation, and bone reference acquisition and balancing, which are distinct from those performed during manual TKA, some surgical steps are not required, such as drilling the femoral canal or setting up an extra/intramedullary tibial guide [38][39][40]. Therefore, it is reasonable to obtain an overall similar operative time between the two methods.…”
Section: Discussionmentioning
confidence: 99%